How to create solid rights for forest carbon transactions: Challenges for the implementation of the REDD+ program in Peru - Wieland Fernandini, Patrick (2014)
Over time, forests have played an important role in the ecosystems’ balance.   They store and retain a large amount of carbondioxide, preventing it to be released into the atmosphere. However, in recent years, deforestation and forest     degradation endanger their continuity in the provision of such service.In this article, the authors explain the program called “Reducing emissions from deforestation and forest degradation” (REDD+), which seeks to combat such problems. In that way, they introduce  which  are  the  challenges  for its implementation in our country.